(untitled) (Research, Society and Development, 2021)
This article aims to reflect on the proposal for evaluating learning from neoliberal policies implemented by the Common National Curriculum Base (BNCC). The methodology was developed through a qualitative field research, having as universe, three educational institutions of the municipal public network of a city in Bahia. The resources for collecting the information were document analysis and semi-structured interviews carried out with three pedagogical coordinators. The scrutiny of information took place through content analysis, grouped into two final categories. The results indicate that the assessment of learning in the BNCC field points to two directions: as a reference to managerialism and control and as a training pedagogical resource. The research participants perceive the evaluative practice as a fundamental tool for monitoring the student’s school life, but they did not show security when dealing with this from the perspective of the Base.